MATERNAL AND FETAL RISK FACTORS ASSOCIATED WITH LATE PRETERM INFANTS - Luísa Krusser Vanin; Helen Zatti; Thaise Soncini; Rodrigo Dias Nunes; Louise Beni Staudt de Siqueira (Sociedade de Pediatria de São Paulo, 2019)
ABSTRACT Objective: To determine maternal and fetal risk factors associated with the birth of late preterm infants in comparison to those born at term. Methods: A case-control study was carried out in a tertiary center for high-risk pregnancies. For the cases, the study enrolled post-partum mothers and their respective newborns with gestational ages equal or greater than 34 weeks and less than 37 weeks. As controls, the post-partum mothers and their newborns with gestational ages of 37 weeks or greater were selected. The sample was calculated with a ratio of two controls for each case, resulting in 423 patients. Association studies were performed using the chi-square test or Fisher's exact test and logistic regression analysis. Results: The variables associated with late prematurity were inadequate prenatal (Odds Ratio [OR] 1.23; confidence interval of 95% [95%CI] 1.12-1.34; p≤0.001), premature rupture of membranes (OR 4.98; 95%CI 2.66-9.31; p≤0.001), length of hospital stay ≥24 hours until birth (OR 0.18; 95%CI 0.06-0.52; p≤0.001), cesarean section (OR 2.74; 95%CI 1.69-4.44; p≤0.001) and small for gestational age newborn (OR 3.02; 95%CI 1.80-5.05; p≤0.001). Conclusions: Inadequate prenatal care and membranes' premature rupture were found as factors associated with the late preterm birth. It is important to identify the factors that allow intervention with adequate prenatal care in order to reduce poor outcomes due to late prematurity.